Debasement of district councils in Kerala: commentary
Short of abolishing the district councils altogether, the various amendments made to the District Administration Act of Kerala by the present Congress (I)-led government do everything to negate them, to make them functionless, powerless and completely dependent on the state government for finance. Reproduced
Keywords: Kerla; District Council; District Administration; District Administration - India - Kerala